HUBUNGAN JENIS PERSALINAN DENGAN KEBERHASILAN INISIASI MENYUSUI DINI (IMD) DI RSUD H. DAMANHURI BARABAI - St. Rusmadiyah; Zakiah; Fitria Jannatul Laili; Suhrawardi (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2026)
Early Initiation of Breastfeeding (EIB) is a crucial step for breastfeeding success and reducing the Infant Mortality Rate (IMR). However, its implementation still faces obstacles, especially in deliveries involving Sectio Caesarea (SC) compared to normal deliveries. EIB is the process of providing breast milk to infants within one hour after birth. The implementation of Early Initiation of Breastfeeding (EIB) is closely related to exclusive breastfeeding. Infants who undergo EIB have a 66% potential to receive exclusive breastfeeding. At RSUD H. Damanhuri Barabai, EIB coverage has shown an increase but still needs to be optimized to reach national targets. This study aims to determine the relationship between the type of delivery and the success of Early Initiation of Breastfeeding (EIB) at RSUD H. Damanhuri Barabai. This study used a quantitative design with a cross-sectional approach. The study population consisted of women giving birth at RSUD H. Damanhuri Barabai, with a total sample of 142 respondents. Data processing was conducted univariately to observe frequency distribution and bivariately using the Chi-Square statistical test. The results of this study showed that the majority of respondents had a normal delivery (56.3%) and the remainder underwent SC (43.7%). A total of 104 respondents (73.24%) successfully performed EIB, with a success rate of 83.75% in normal deliveries and 59.67% in SC deliveries. The Chi-Square statistical test results showed a p-value of 0.001 (p < 0.05). There is a significant relationship between the type of delivery and the success of Early Initiation of Breastfeeding (EIB) at RSUD H. Damanhuri Barabai. Normal delivery has a higher probability of EIB success compared to Sectio Caesarea delivery. Type of Delivery, EIB Success, Sectio Caesarea, Normal Delivery.